Molecular cytogenetic characterization of del(X)(p22.33)mat and de novo dup(4)(q34.3q35.2) in a male fetus with multiple anomalies of facial dysmorphism, ventriculomegaly, congenital heart defects, short long bones and clinodactyly - Chih-Ping Chen; Jian-Pei Huang; Yi-Yung Chen; Shin-Wen Chen; Schu-Rern Chern; Peih-Shan Wu; Fang-Tzu Wu; Yen-Ting Pan; Wen-Lin Chen; Chen-Wen Pan; Wayseen Wang (Elsevier, 2023)
Objective: We present molecular cytogenetic characterization of del(X) (p22.33)mat and de novo dup(4) (q34.3q35.2) in a male fetus with multiple anomalies of facial dysmorphism, ventriculomegaly, congenital heart defects, short long bones and clinodactyly. Case report: A 36-year-old, gravida 3, para 1, woman with short stature (152 cm) underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 46,Y,del(X)(p22.33)mat, dup(4)(q34.3q35.2). The mother had a karyotype of 46,X,del(X)(p22.33). Array comparative genomic hybridization (aCGH) analysis on the DNA extracted from cultured amniocytes revealed arr Xp22.33 × 0, 4q34.3q35.2 × 3. Prenatal ultrasound at 23 weeks of gestation revealed multiple anomalies of flat nasal bridge, ventriculomegaly, atrioventricular septal defect (AVSD) and clinodactyly. The pregnancy was subsequently terminated, and a malformed fetus was delivered with facial dysmorphism. Cytogenetic analysis of the umbilical cord revealed 46,Y,del(X)(p22.33)mat, dup(4)(q34.3q35.2)dn. aCGH analysis on the DNA extracted from the umbilical cord revealed arr [GRCh37 (hg19)] 4q34.3q35.2 (181,149,823-188,191,938) × 3.0, arr Xp22.33 (470,485-2,985,006) × 0 with a 7.042-Mb duplication of 4q34.3-q35.2 and a 2.514-Mb deletion of Xp22.33. Conclusion: A male fetus with del(X)(p22.33) and dup(4)(q34.3q35.2) may present congenital heart defects and short long bones on prenatal ultrasound.